Investigation of ultraviolet aging resistance of bitumen modified by layered double hydroxides with different particle sizes. (30th January 2019) - Cao, Zhilong; Chen, Meizhu; He, Bianyang; Han, Xiaobin; Yu, Jianying; Xue, Lihui
Highlights: Layered double hydroxides (LDHs) with different particle size are used to modify bitumen. The ultraviolet shielding property of LDHs with the average diameter of 180 nm is better than that with other particle size. The LDHs with the average diameter of 180 nm is more beneficial to enhance the UV aging resistance of bitumen than that with other particle size. Abstract: Layered double hydroxides (LDHs) with different particle sizes (75 nm, 115 nm, 180 nm and 300 nm which were marked with LDHs-75, LDHs-115, LDHs-180 and LDHs-300) were characterized by scanning electron microscope, UV–vis reflection and absorption spectrophotometer and laser scatter meter. Furthermore, this paper investigated the influence of LDHs with different particle sizes on the rheological properties of bitumen before and after ultraviolet aging by temperature susceptibility test, dynamic shear rheometer test (DSR) and IR spectra test (FTIR). The researches reveal that LDHs-180 hold the strongest UV shielding performance. The temperature susceptibility of pristine bitumen and LDHs-75, LDHs-115, LDHs-180, LDHs-300 modified bitumen after aging decreased by 9.01%, 6.36%, 3.98%, 2.15% and 5.49%, respectively, which indicate LDHs-180 is more beneficial to weaken the decrease of bitumen temperature susceptibility after aging. Similarly, LDHs-180 modified bitumen show less variation in rheological properties than other bitumen samples after aging. This implies that LDHs-180 could mitigate the influences of UV aging on the rheological properties of bitumen more availably. In addition, the FTIR analysis further shows that the carbonyl and sulfoxide index of LDHs-180 modified bitumen is the smallest after aging, which indicates LDHs-180 is more helpful for improving bitumen anti-UV aging properties than that of LDHs-75, LDHs-115 and LDHs-300.